Magnetic Resonance Imaging Characterization of the Hippocampi in Temporal Lobe Epilepsy: Correlation of Volumetry and Apparent Diffusion Coefficient with Laterality and Duration of Seizures - Muralidhar, Apoorva; Kumar, Ashok; Prakash, Arjun; Krishnamurthy, Umesh; S., Manjunath; Majeed, Roshni (Indian Journal of Radiology and Imaging, 2021)
Background and Purpose It is estimated that hippocampal damage is seen in 50 to 70% of patients with temporal lobe epilepsy (TLE). Although most magnetic resonance imaging (MRI) studies are adequate to detect gross hippocampal atrophy, subtle changes that may characterize early disease in TLE, such as visually nonappreciable volume loss, may often be missed if objective volumetric analysis is not undertaken.Materials and Methods We conducted a hospital-based prospective analytical study in which 40 patients with partial seizures of temporal lobe origin were included and their hippocampal volumes (HVs) were determined by manual volumetric analysis. The findings were recorded and correlated with the side of seizure and its duration. The quantitative assessment was allotted different grades accordingly. Also, the apparent diffusion coefficient (ADC) values of bilateral hippocampi were estimated and their correlation with the side of seizure was determined.Results Most patients in the study were in the age group of 11 to 20 years (37.5%). In total, 57.5% had seizures for a period of 1 to 5 years. While 67.5% (n = 27) had seizure on the right, 32.5% (n = 13) had on the left. The mean HV estimated on the right and left were correlated with the side of seizure and found to be statistically significant (p < 0.001 in those with right-sided seizures and p = 0.02 in those with left-sided seizures). Simultaneously the ADC values estimated were found to correlate with the laterality of seizures with a statistical difference (p < 0.01). Duration of seizures however did not show a positive correlation with the HV.Conclusion MRI with quantitative estimation of HV and ADC values can depict the presence and laterality in TLE with accuracy rates that exceed those achieved by visual inspection alone. Thus, quantitative MRI provides a useful means for translating volumetric analysis into clinical practice.
Keywords: apparent diffusion coefficient; hippocampal atrophy; hippocampal volume; volumetry; mesial temporal sclerosis; temporal lobe epilepsy